2008
DOI: 10.1080/14622200801901971
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of depressive symptoms and smoking cessation

Abstract: Because different psychopathologic components of depressive symptoms may have distinct etiologies, examining their differential effects on smoking cessation may elucidate mechanisms underlying the smoking-depression relationship. Negative affect (NA), somatic features (SF), low positive affect/anhedonia (PA), and interpersonal disturbance (IP) have been identified as unique dimensions of depression that can be measured using the Center for Epidemiologic Studies Depression Scale (CESD). This study examined comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
202
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(227 citation statements)
references
References 70 publications
18
202
6
1
Order By: Relevance
“…In any event, if some smokers do experience a loss of interest in nondrug rewards and pleasures (anhedonia) during early cessation and are able to reverse this by smoking, then they are likely to be at elevated risk of relapse (e.g. Leventhal et al, 2008).…”
Section: Salience Attribution Attentional and Motivational Responsesmentioning
confidence: 99%
“…In any event, if some smokers do experience a loss of interest in nondrug rewards and pleasures (anhedonia) during early cessation and are able to reverse this by smoking, then they are likely to be at elevated risk of relapse (e.g. Leventhal et al, 2008).…”
Section: Salience Attribution Attentional and Motivational Responsesmentioning
confidence: 99%
“…Only one longitudinal study has examined positive affect among participants in a smoking cessation treatment program. For each one-unit reduction in positive affect at baseline, participants were 9% less likely to be abstinent 26 weeks after their planned quit date (Leventhal, Ramsey, Brown, LaChance, & Kahler, 2008). Analyses controlled for nicotine dependence, number of cigarettes smoked per day, negative affect, and depression.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…1 It has been demonstrated that anhedonia, or the absence of positive affect, predicts difficulty quitting above and beyond other dimensions of depression. 2 Anhedonia is also associated with greater withdrawal symptoms and cigarette cravings during a quit attempt. 3,4 Anhedonic smokers may have a heightened bias toward the rewarding value of smoking, which may serve as a primary reinforcing mechanism for smoking behavior.…”
Section: Introductionmentioning
confidence: 99%